Treatment results in patients with extravasal compression of celiac trunk and its atherosclerotic lesion - Yu. G. Starkov; A. V. Pokrovskiy; S. V. Dzhantukhanova; I. E. Timina; A. F. Kharazov; R. D. Zamolodchikov; N. Yu. Glagoleva («REMEDIUM GROUP» Ltd., 2020)
Introduction. Extravasal compression of celiac trunk is the cause of chronic abdominal ischemia syndrome (CAIS) along with atherosclerotic lesions of the visceral branches of the aorta. Patients with isolated compression and those in the older age group with compression combined with atherosclerotic lesion are distinguished. At present, the issues of indications for surgical treatment the pattern and technique of surgical intervention as well as the evaluation of decompression results in the early and distant postoperative period remain controversial and unsolved.Aim. The aim of our study was to determine indications and contraindications for surgical intervention, to improve the technique of the surgery, to evaluate and find ways to improve the closest and most distant results of laparoscopic decompression of the celiac trunk.Materials and methods. The article discusses the experience of performing 27 laparoscopic decompressions of the celiac trunk and the results of examination and treatment of 5 patients who underwent endovascular interventions due to a combined lesion -extravasal compression of the celiac trunk and atherosclerotic occlusion. Intraoperative laparoscopic ultrasound was performed in all cases of the celiac trunk decompression to determine the celiac trunk topography and assess the adequacy of its decompression.Results. The average duration of the surgery was 92 minutes. Intraoperative and early postoperative complications were not observed. Intraoperative blood loss didn't exceed 50 ml. Average duration of stay in the hospital was 5 days. According to the data of ultrasound examination, the average degree of celiac trunk compression before the operation was 76%, in the early postoperative period it decreased to 43%, and in the distant period it decreased to 32%.Discussion. Based on our experience, the key to successful management of patients with celiac trunk compression syndrome is a multidisciplinary approach to diagnosis and treatment. Patients need thorough differential diagnosis, including psychoneurologist consultation. Experience in treating patients with atherosclerotic lesions of the celiac trunk combined with extravasal compression has shown good immediate and distant decompression results and adverse results of the first stage of endovascular interventions.Conclusion. Laparoscopic decompression of the celiac trunk is an effective treatment method in patients without atherosclerotic lesions.